Increasing Production Machine Capacity In Food Product Msmes Using A Linear Proramming Approach - Sihotang, Farida (JUEB : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to optimize production capacity in a small and medium-sized enterprise (SME) that produces three types of meatballs: beef meatballs, chicken meatballs, and fish meatballs, by considering both cost aspects and demand fulfillment. A mathematical model was developed to minimize total costs, including operational costs, machinery costs, capacity expansion costs, loss costs, and outsourcing costs. Decision variables include the optimal quantity of demand fulfilled, , actual cycle time, the total number of machines operated, and the number of additional machines required. The optimization results show an objective function value of IDR 89,065,838, achieved through selective machine additions and the use of overtime during peak periods. Chicken meatball production exhibited a steady increase without requiring overtime, while beef and fish meatballs required overtime in certain periods. Sensitivity analysis indicates that normal operational costs are the most influential factor affecting total costs, followed by machinery costs and overtime costs. These findings emphasize the importance of proper capacity planning, cost control, and efficient production scheduling strategies to ensure sustainable demand fulfillment.